The Effect of Health Insurance on Health Care Utilization: Evidence from The Medical Expenditure Panel Survey 2000-2005 - Beuermann, Diether W. (2010)
This paper exploits the fact that insurance eligibility in the United States changes abruptly at age 65 due to universal coverage provided by Medicare. In that way, we adopt a regression discontinuity design to analyze the effect of health insurance coverage on health care access and utilization. The main findings suggest that groups with lower pre-65 coverage gain higher increases in the probability of being insured at 65. For instance, less educated persons (less likely to have pre-65 health insurance) appear to increase their likelihood of being insured at age 65 by more than their more highly educated counterparts. Furthermore, this increased insurance coverage appears to be associated with reductions in intergroup disparities in health care access. Therefore, the findings suggest that insurance matters in order to access health care services in a way that could potentially reduce inequalities between different ethnic groups.